The transitory nature of parent, sibling and romantic partner relationships in emerging adulthood - Milevsky, Avidan (SpringerBriefs in Well-Being and Quality of Life Research, 2014)
This volume provides a theoretical and empirical review of the societal and educational factors that contribute to 'emerging adulthood'. This developmental stage occurs between adolescence and adulthood, and can be regarded as a relatively new phase in research on development. The book specifically examines how these societal and educational changes have contributed to the transitory nature of emerging adulthood and the resulting consequences. Particular attention is paid to the transitory nature of this stage of life, primarily in regard to relationship dynamics. The book examines the nature of the parental relationship during emerging adulthood. It uses qualitative data from a recent phenomenological study to illustrate unique aspects of the parental relationship during this stage and discusses the findings in the context of existing empirical work. The book provides a holistic and thorough examination of emerging adulthood in general and the parental dynamics present during this stage, in particular. Co-Authors: Kristie Thudium Jillian Guldin, MA